KEPEMIMPINAN KEPALA SEKOLAH DALAM PENGEMBANGAN LEMBAGA PENDIDIKAN ISLAM DI MTS NAHDATUL ULAMA MARON - Siti Sofiyah; Taufik Hidayat (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to reveal the types of school leadership, creative efforts in developing creative and superior educational institutions, with sub-focus including: (1) What type of leadership does the principal apply in development? Islamic education institutions at MTS NU Creative (2) efforts have been made to develop the main institution for Creative Islamic Education at MTS NU and (3) the desired output target for Muhtadin Creative elementary schools. This study uses qualitative research in the form of case studies. Data collection is done by interview, observation, and documentation. As for data analysis techniques, researchers use an interactive model that contains four interrelated components, namely: data collection, data simplification, data presentation, and drawing conclusions and submissions. The results of the study show that: (1) the type of school principal who applies Muhtadin's creative leadership, democratic leadership (accommodative, aspirational, assertive and open), where the principal during leadership is able to make changes and has a vision for the future of Islamic education institutions to develop MTS NU Creative schools towards creative and superior schools; (2) all the efforts made in developing the main institution of Creative Islamic Education MTS NU elementary schools to build a school system; (3) what are the output targets desired by MTS Nahdatul Ulama, namely: initial output (Initial Results) and including general output targets.